2021
DOI: 10.3390/ijerph18158123
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection Methods for Silicosis in Australia and Internationally: A Review of the Literature

Abstract: Pneumoconiosis, or occupational lung disease, is one of the world’s most prevalent work-related diseases. Silicosis, a type of pneumoconiosis, is caused by inhaling respirable crystalline silica (RCS) dust. Although silicosis can be fatal, it is completely preventable. Hundreds of thousands of workers globally are at risk of being exposed to RCS at the workplace from various activities in many industries. Currently, in Australia and internationally, there are a range of methods used for the respiratory surveil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 72 publications
0
19
0
3
Order By: Relevance
“…Exposure is very common in low- and middle-income countries [ 2 ]. The lack of early detection of silicosis leaves us with a continuing need for exploration when confronted with silicosis [ 29 ]. The results suggest that although some preventive measures for silicosis are known, exposure to risk factors has been ignored, leading to the development of silicosis [ 30 ] and an increase in the number of deaths.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure is very common in low- and middle-income countries [ 2 ]. The lack of early detection of silicosis leaves us with a continuing need for exploration when confronted with silicosis [ 29 ]. The results suggest that although some preventive measures for silicosis are known, exposure to risk factors has been ignored, leading to the development of silicosis [ 30 ] and an increase in the number of deaths.…”
Section: Discussionmentioning
confidence: 99%
“…Chest X-rays (CXRs), high-resolution computed tomography (HRCT), pulmonary function tests (PFT), and health and exposure questionnaires are the major methods for the respiratory surveillance of workers exposed to RCS. However, these methods cannot detect the disease until it has significantly progressed [ 29 ]. Although it has been reported that CXR cannot reliably detect occupational lung diseases [ 30 ], it is still recommended in the diagnosis of silicosis by the International Labour Organisation (ILO) Classification System [ 31 ].…”
Section: Clear Causes and Unresolved Mechanisms Of Silicosismentioning
confidence: 99%
“…They would also be benefitted initiating similar silicosis intervention programme in their countries using CC16 or similar marker for early detection as suggested by a recent study. 22 International organizations such as WHO, The Union, etc, should come forward coordinating and guiding member countries and taking this matter forward further in order to achieve the desired goal. The concept of secondary prevention of silicosis using an effective screening tool such as serum CC16 may be validated in above-said countries to establish its potential benefits both nationally as well as internationally.…”
Section: Policy Decision Toward Control Of Silicosismentioning
confidence: 99%